2003
DOI: 10.17705/1cais.01221
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Intelligence and the Web

Abstract: Competitive intelligence (CI) is the selection, collection, interpretation and distribution of publicly held information that is strategically important to a firm. A substantial amount of this public information is accessible via the World Wide Web. This paper describes some of the difficulties in using this information resource for CI purposes, some of the solutions to these difficulties, and areas in need of research if the Web is to be used in CI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 10 publications
0
16
0
1
Order By: Relevance
“…• Establishing security: The security of mission-critical corporate intelligence systems [Boncella, 2003] • Designing scalable systems: The scalability of Web-based systems when large volumes of BI information are exchanged between databases and Web clients [Cody, 2002].…”
Section: Research Issuesmentioning
confidence: 99%
“…• Establishing security: The security of mission-critical corporate intelligence systems [Boncella, 2003] • Designing scalable systems: The scalability of Web-based systems when large volumes of BI information are exchanged between databases and Web clients [Cody, 2002].…”
Section: Research Issuesmentioning
confidence: 99%
“…The official information (Boncella 2003): -the reports, publications, editions, staff of the company; -publications in the press; -the official events, which are organized by the company (exhibitions, seminars, presentations); -the production and services; -official telephone conversations with the representatives of the company; -publicity and the materials, which are delivered; -commercial offers; -the information, which is put in the Internet; -statistical information; -technical transmitters of the information, information technologies and their equipments (TV, the radio); -the materials of the exhibitions etc.…”
Section: The Role Of Information and The Sources In The Business Modementioning
confidence: 99%
“…This is an ongoing research project and so far the body of knowledge in the literature addressing this research topic is very limited. Jakubchak [30] has conducted a research to estimate the value of using multi-criteria analysis for intelligence analysts in the military domain. This research tested empirically with controlled experiments the value of using MCDA to support analysts in their intelligence work and conclude that it is likely to be a valuable method to use when conducting intelligence analysis.…”
Section: Critical Issuesmentioning
confidence: 99%
“…The term was defined by the Society of Competitive Intelligence Professionals as "a systematic and ethical program for gathering, analyzing and managing external information that can affect your company's plans, decisions and operations". After a large review of the literature, we found that no single definition of CI is likely to be precise and universally accepted [30,31,32,33]. CI is divided in three categories [1]:…”
Section: Introductionmentioning
confidence: 99%